Strategies to Improve Employee Motivation and Performance Through the Employee Engagement Program - Nendi, Ikhsan; Abdurokhim, Abdurokhim; Askarno, Askarno (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Employee motivation and performance are two important factors that determine the success of a company. Motivated and high-performing employees will produce high productivity and help the company achieve its goals. However, in reality, not all employees are always motivated and high performing. The aim of this research is to analyze the influence of employee engagement programs on employee motivation and performance. This research uses quantitative research methods. The approach used is a case study. Data collection techniques in this research are literature study and questionnaires. The data that has been collected is then analyzed using the SPSS program. The results of the research show that the employee management program has a positive and significant effect on the motivation and performance of employees at Company X. The employee engagement program is an effective strategy for increasing the motivation and performance of employees at Company Work.